Design of a multi-epitope recombinant BCG vaccine targeting Brucella OMP31, LptE and VirB2 in immunoinformatics approaches - Chuang Li; Yuejie Zhu; Xingxing Qi; Zhenglong Chai; Jiarui Luo; Kaiyu Shang; Tingting Tian; Huidong Shi; Mingzhe Li; Ruixue Xu; Fuling Pu; Junyu Kuang; et al. (PLoS ONE, 2025)
Brucellosis, caused by the intracellular pathogen Brucella , remains a significant health challenge, alongside substantial economic impacts on livestock industries. Despite antibiotic treatments, the absence of licensed human vaccines necessitates innovative preventive strategies. In this study, we employed reverse vaccinology to design a novel multi-epitope vaccine (MEV) targeting Brucella melitensis . Three immunogenic proteins—outer membrane protein OMP31, LPS assembly protein LptE, and the type IV secretion system protein VirB2—were selected as vaccine candidates. Comprehensive bioinformatics analysis identified six cytotoxic T lymphocyte (CTL) epitopes, nine helper T lymphocyte (HTL) epitopes, seven linear B-cell epitopes, and five conformational B-cell epitopes. The incorporation of molecular adjuvants (cholera toxin B subunit and PADRE) served to further enhance the immunogenicity of the vaccine. Given that Brucella is an intracellular parasite, TAT cell-penetrating peptides were added to further enhance the intracellular delivery of MEV. The constructed MEV has been shown to have excellent antigenicity (VaxiJen score >0.8), stability (instability index <40), solubility (Protein-Sol score: 0.87) and hydrophilicity (GRAVY index: −0.319), and is non-allergenic. Structural optimization, including disulfide bond engineering (11 pairs of residues), improved molecular stability, with molecular docking and dynamics simulations confirming robust interactions with immune cell receptors (docking score: −311.85). Using SnapGene 7.1.2, we performed in silico cloning simulation of the codon-optimized multi-epitope vaccine (MEV) sequence into the pMV261 shuttle vector, generating a recombinant BCG (rBCG) construct. Immunoinformatics simulations (C-ImmSim) demonstrated potent immune activation, with significant increases in cytotoxic T cells (1050 cells/mm³), memory helper T cells (1150 cells/mm³), and IFN-γ production (2 × 10^6 ng/ml), alongside sustained IgG/IgM titers over 350 days(1 × 10^5 cells/mm 3 ) . Furthermore, the recombinant BCG multi-epitope Brucella vaccine, developed through bioinformatics approaches, demonstrates promising characteristics and immunogenicity. Nevertheless, its immunological efficacy requires to further experimental validation.